♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
![f(x) = 2x + 3](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%20%2B%203)
And
![g(x) = 2 \times {3}^{x} \\](https://tex.z-dn.net/?f=g%28x%29%20%3D%202%20%5Ctimes%20%20%7B3%7D%5E%7Bx%7D%20%20%5C%5C%20)
_________________________________
To find the y-intercept of any equation just need to put 0 (( zero )) instead of the x in the equation...
<h2>
Let's do it....</h2>
_________________________________
In f ( x ) :
![y - intercept = f(0)](https://tex.z-dn.net/?f=y%20-%20intercept%20%3D%20f%280%29)
![f(x) = 2x + 3](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%20%2B%203)
![f(0) = 2(0) + 3](https://tex.z-dn.net/?f=f%280%29%20%3D%202%280%29%20%2B%203)
![f(0) = 3](https://tex.z-dn.net/?f=f%280%29%20%3D%203)
Thus :
![y - intercept = 3](https://tex.z-dn.net/?f=y%20-%20intercept%20%3D%203)
##############################
In g ( x ) :
![y - intercept = g(0)](https://tex.z-dn.net/?f=y%20-%20intercept%20%3D%20g%280%29)
![g(x) = 2 \times {3}^{x}](https://tex.z-dn.net/?f=g%28x%29%20%3D%202%20%5Ctimes%20%20%7B3%7D%5E%7Bx%7D%20)
![g(0) = 2 \times {3}^{0}](https://tex.z-dn.net/?f=g%280%29%20%3D%202%20%5Ctimes%20%20%7B3%7D%5E%7B0%7D%20)
![g(0) = 2 \times 1](https://tex.z-dn.net/?f=g%280%29%20%3D%202%20%5Ctimes%201)
![g(0) = 2](https://tex.z-dn.net/?f=g%280%29%20%3D%202)
Thus :
![y - intercept = 2](https://tex.z-dn.net/?f=y%20-%20intercept%20%3D%202)
_________________________________
The positive difference in the y-intercept value of f ( x ) and g ( x ) is :
![|3 - 2| = |1| = 1](https://tex.z-dn.net/?f=%20%7C3%20-%202%7C%20%20%3D%20%20%7C1%7C%20%20%3D%201)
So write this in the box : 1
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️
And we're done....
♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️